Comparison of optimal solvent extraction stages between P204 and [A336][P204] for the separation of europium and gadolinium - Ismail, N. A.; Mohd Yunus, M. Y.; Abd Aziz, Mohd Aizudin (IOP Publishing, 2019)
This study was designed to compare between the number of extraction stages required by 2-ethylhexyl phosphoric acid mono 2-ethylhexyl ester P204 and ionic liquid-based system of [A336][P204] in a cascade counter-current extraction process for the separation of europium (Eu) and gadolinium (Gd). Eu and Gd were chosen for this study as these metals are among the strenuous due to low availability in nature and small separation factor. The value of the separation factor (β) of both extractants, was obtained from the experimental work, while other process parameters were calculated using the counter-current model developed by Xu Guangxian. Extraction of Eu using [A336][P204] was found optimum at 3.5 M of nitric acid, with organic to aqueous (O/A) ratio of 9:1, while the optimum condition for P204 was determined at 3.0 M of hydrochloric acid and 9:1 of O/A ratio. The optimized β value for P204 was identified lower (β:2.38) compared to the condition for [A336][P204] (β:3.44). In order to obtain the optimal number of separation stages, the target purity and recovery rates were set to 99.9% and 90% respectively for both extractants. From the Xu model, the results show that [A336][P204] extractant requires at a minimum of four and two extraction and scrubbing stages respectively for maintaining the desired outputs. Meanwhile, P204 extractant needs to develop at least eight extraction stages as well as five scrubbing stages to produce the same production capacity. This finding generally suggests that [A336][P204] is favorable over P204 for the separation of europium and gadolinium particularly from the viewpoint of economic interest.